If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (4y + 7)(9 + -1y) = 0 Reorder the terms: (7 + 4y)(9 + -1y) = 0 Multiply (7 + 4y) * (9 + -1y) (7(9 + -1y) + 4y * (9 + -1y)) = 0 ((9 * 7 + -1y * 7) + 4y * (9 + -1y)) = 0 ((63 + -7y) + 4y * (9 + -1y)) = 0 (63 + -7y + (9 * 4y + -1y * 4y)) = 0 (63 + -7y + (36y + -4y2)) = 0 Combine like terms: -7y + 36y = 29y (63 + 29y + -4y2) = 0 Solving 63 + 29y + -4y2 = 0 Solving for variable 'y'. Factor a trinomial. (9 + -1y)(7 + 4y) = 0Subproblem 1
Set the factor '(9 + -1y)' equal to zero and attempt to solve: Simplifying 9 + -1y = 0 Solving 9 + -1y = 0 Move all terms containing y to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + -1y = 0 + -9 Combine like terms: 9 + -9 = 0 0 + -1y = 0 + -9 -1y = 0 + -9 Combine like terms: 0 + -9 = -9 -1y = -9 Divide each side by '-1'. y = 9 Simplifying y = 9Subproblem 2
Set the factor '(7 + 4y)' equal to zero and attempt to solve: Simplifying 7 + 4y = 0 Solving 7 + 4y = 0 Move all terms containing y to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + 4y = 0 + -7 Combine like terms: 7 + -7 = 0 0 + 4y = 0 + -7 4y = 0 + -7 Combine like terms: 0 + -7 = -7 4y = -7 Divide each side by '4'. y = -1.75 Simplifying y = -1.75Solution
y = {9, -1.75}
| 3+4k-3k= | | x-(-2)=-7 | | -7y+5=8y+8 | | 4(3x+-5)+6=12x-14 | | 91-2x=9x-162 | | 5(9+-5.5)+3y=-4 | | 8x+11=6x+13 | | 2m+(-8m)= | | 5y-6x=-13 | | 4/5+1/8= | | (5n-20)=3n | | -x-6=-2x-1 | | D+5=3 | | 3k^2-10k+3=0 | | x+2=48 | | 256x+1=125x-2 | | 2/3x-1+1/6=9 | | 6x^3+14x^2-21x-49=0 | | x=3x+6x | | x=3x-6x | | x=3x-5-5x-26 | | 4-(12+z)=192 | | y-8=(x-6) | | x=3x-5+5x-26 | | 12y+8=24 | | 3(x-5)=x+8-5 | | r+31=17 | | 9=-4+v | | 10+6x=3x+16 | | z+15=78 | | -50=-4x-20-2x | | 9+5(2w-1)=-3(2w-2)+2w |